Treatment for Residual Rhotic Errors With High- and Low-Frequency Ultrasound Visual Feedback: A Single-Case Experimental Design - Preston, Jonathan L.; McAllister, Tara; Phillips, Emily; Boyce, Suzanne; Tiede, Mark; Kim, Jackie S.; Whalen, Douglas H. (Journal of speech, language, and hearing research, 2018)
Purpose: The aim of this study was to explore how the frequency with which ultrasound visual feedback (UVF) is provided during speech therapy affects speech sound learning. Method: Twelve children with residual speech errors affecting [alveolar approximant] participated in a multiple-baseline across-subjects design with 2 treatment conditions. One condition featured 8 hr of high-frequency UVF (HF; feedback on 89% of trials), whereas the other included 8 hr of lower-frequency UVF (LF; 44% of trials). The order of treatment conditions was counterbalanced across participants. All participants were treated on vocalic [alveolar approximant]. Progress was tracked by measuring generalization on [alveolar approximant] in untreated words. Results: After the 1st treatment phase, participants who received the HF condition outperformed those who received LF. At the end of the 2-phase treatment, within-participant comparisons showed variability across individual outcomes in both HF and LF conditions. However, a group level analysis of this small sample suggested that participants whose treatment order was HF-LF made larger gains than those whose treatment order was LF-HF. Conclusions: The order HF-LF may represent a preferred order for UVF in speech therapy. This is consistent with empirical work and theoretical arguments suggesting that visual feedback may be particularly beneficial in the early stages of acquiring new speech targets.